ANALYSIS OF THE ADOPTION OF WHEAT SOWING RECOMMENDATIONS AMONG SMALL FARMERS USING WATER SAVING INTERVENTIONS - N. Mahmood; T. Ali; M.S. Bajwa; M .Shahbaz; M. B. Chattha (Journal of Animal and Plant Sciences, 2013)
Wheat is a staple food crop of Pakistan. Enhancing wheat yield by encouraging farmers, predominantly small farmers, to adopt agricultural innovations including efficient and judicious use of land and water resources for coping with the needs and demands of ever increasing population of Pakistan is a serious challenge. This challenge provided impetus to plan and conduct the present study. In order to evaluate the adoption of the latest technologies at small farms, district Faisalabad was selected as the study area. Area under study comprised five tehsils: Faisalabad, Jaranwala, Sammandri, Chak Jhumra and Tandlianwala. The cross sectional survey research design was applied. Field interviews were conducted with the help of a validated and reliable research instrument. Most of the respondents (58%) under observation were of middle age category. Majority of the respondents (~100%) adopted wheat sowing recommendations such as well preparation of soil, use of recommended dose of seed, application of fertilizer, best way of harvesting and better method of storage whereas, manual weed removing, and fumigation of seed were adopted 33.0% and 37.8 %respectively. Further more regarding extent of adoption of wheat sowing recommendations, the well preparation of soil and best method of storage were adopted by 84.4 %, and 63.7% respondent respectively where as the respondent adopted the wheat sowing recommendations such as use of recommended seed (56.3%) and use of weedicide (55.6%) to an average extent. Compatibility of farmers’ preferences with the recommendations and actual practices provide useful adoption indicators.
Keywords: Adoption; Wheat; Recommendations; Small farmers; Faisalabad